PESAN DALAM PROGRAM KOTA KREATIF DAN SIKAP FOLLOWERS TERHADAP PENGEMBANGAN EKONOMI KREATIF - Adzkia Kirana Dipa; Hanny Hafiar; Anwar Sani (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2020)
Kota Kreatif Program is a program that is followed by selected cities in Indonesia to support the development of the creative economyThe aim of this study is to acknowledge the correlation between the message in the Message in the Program Kota Kreatif on instagram @kominfopadangpanjang account with behavior of followers toward economy creative develpoment. This study used AISAS and correlation method with descriptive and inferential statistical analysis. The amount of samples was 93 people which was obtained by simple random sampling technique. The data was obtained by questionnaire, interview, and literature review. The result of this study was that there was strong correlation between Message in the Program Kota Kreatif with behavior of followers toward economy creative develpoment. The conclusions of this study was that there was strong relationship between the campaign message Program Kota Kreatif with attentio aspect, and a significant relationship between the campaign message Program Kota Kreatif with interest aspects, search aspect, action aspect and share aspects. Based on these conclusions, the researcher suggests that the target is young women and college student. with complete information message and improvement on visualization quality, and message on video format.